2014
DOI: 10.1097/brs.0000000000000388
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and Mechanical Comparisons of Lumbar Hybrid Fixation Using Dynesys and Cosmic Systems

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…However, no signi cant between-group di erence was found in CASD, which indicated that topping-o technique was more e ective in preventing radiographical parameters. is may be explained by the decrease of compensatory mechanisms in the segmental range of motion in the topping-o group [34,43]. Our results showed that postoperative GLL was similar in the topping-o group and PLIF group.…”
Section: Discussionmentioning
confidence: 50%
“…However, no signi cant between-group di erence was found in CASD, which indicated that topping-o technique was more e ective in preventing radiographical parameters. is may be explained by the decrease of compensatory mechanisms in the segmental range of motion in the topping-o group [34,43]. Our results showed that postoperative GLL was similar in the topping-o group and PLIF group.…”
Section: Discussionmentioning
confidence: 50%
“…Ideal hybrid stabilization has to preserve normal ROM as much as possible, and the transition segment has to not be too rigid or movable to preserve both the transition and adjacent segments, because a rigid transition segment transfers excessive stress to the adjacent segments from the transition segment. 6,10 At the transition segment, both the IH and PH models suppress the kinematic compensation from the fusion segment and demonstrate smaller ROM and IDP than the fusion model in all loading directions. These values for the PH model were even lower than those for the intact model in all loading directions except under axial rotation, and the IH model showed smaller ROM and IDP than the intact model, especially under extension, because the ISD is designed to distract the foramen.…”
Section: Discussionmentioning
confidence: 98%
“…35 Other studies have concluded that PDS at the adjacent segment was not recommended in patients with clinically asymptomatic ASD. 6,34 A previous meta-analysis also addressed the issue that PDS has no competitive advantage for ASD prevention compared with fusion surgery. 21 However, clinical studies addressing IH demonstrated that IH achieved significantly lower ASD than conventional fusion surgery.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The lumbosacral model from L1 to S1 segments has been developed and validated in the previous studies of the current authors (Chien et al, 2014;Chuang et al, 2012;Chuang et al, 2013). For a paired facet joint, the orientation and separation of the articulating surfaces were cautiously established to ensure a consistent unloaded neutral position within a range of around 0.5 mm.…”
Section: Lumbosacral Modelsmentioning
confidence: 99%